An Investigation of the Needs, Abilities, Opinions, and Anxiety Levels of English Teaching Major Students Studying an English Pronunciation Course in a Blended Learning Environment - Kamsa-ard, Thiratchapon (Journal of Liberal Arts Prince of Songkla University, 2022)
The study investigated the needs and abilities of students taking an English pronunciation course in a blended learning (BL) environment. The students’ opinions toward this course and their anxiety about English pronunciation were also examined. The participants were 72 first-year English teaching major students at Udon Thani Rajabhat University. The instruments consisted of a questionnaire of needs, an ability test, a questionnaire about the students’ opinions, and a questionnaire about the students’ levels of anxiety. The instruments were developed by taking into account both validity and reliability. The findings were as follows. Firstly, the students indicated the highest scores for needs on word stress (x̄ = 4.36) and sentence stress (x̄ = 4.24). Secondly, the scores for word stress in the post-test were significantly higher than those in the pretest (Pre: x̄ = 0.43; Post: x̄ = 0.80), and the sentence stress scores in the post-test were significantly higher than those in the pretest (Pre: x̄ = 0.44; Post: x̄ = 0.80) after implementing BL for word and sentence stress development. Thirdly, the participants were highly satisfied with studying the English pronunciation course in a BL environment (x̄ = 4.25). Fourthly, the student’s anxiety levels significantly lowered (Pre: x̄ = 3.24); Post: x̄ =3.19). This means that the pronunciation course through a BL environment could help reduce pronunciation anxiety.